Pengembangan Buku Panduan Budaya Kerja Berbasis Religius di Sekolah Menengah Kejuruan - Muhamadi, Arif; Dahlan, Bakhrun; Susatya, Edhy; Pamilih, Indra Jamal; Sunarso; Raharjo, Slamet; Hasanah, Noviatun (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Abstract. SMK graduates face challenges in work culture alignment. 5R implementation at SMK Muhammadiyah 2 Jatinom is not yet internalized sustainably. This study aims to develop a religious-based 5R work culture guidebook. The method uses Research and Development (R&D) with the ADDIE model involving 85 teachers and employees, and validation by ten experts. Results show current 5R conditions are at the habituation stage but depend on external supervision. Strategic religious values like amanah and discipline are integrated into 5R elements. The product was declared feasible in the